Simple Yet Efficient: Arylamine‐Terminated Carbazole Donors for Organic Hole Transporting Materials. Issue 12 (14th October 2021) - Liu, Jian; Zhang, Heng; Wu, Bingxue; Sun, Lixue; Chen, Yu; Zong, Xueping; Sun, Zhe; Xue, Song; Liang, Mao
Abstract : The extraordinary electronic and structural properties of carbazole make it an important donor for the molecular design of hole transport materials (HTMs). However, the development of peripheral carbazole donors has lagged behind. Herein, a series of low‐cost arylamine‐substituted carbazole donors are synthesized by a one‐step facile method. The effect of the terminal arylamine on the optoelectronic, thermal stability, hole mobility, and photovoltaic properties of the studied carbazole HTMs is also investigated. The diphenylamine‐ and carbazole‐substituted carbazoles possess the orthogonal–planar conformation, endowing the HTMs (M142 and M143) with excellent electronic properties and morphological properties. Consequently, power conversion efficiencies (PCEs) of 19.60% and 20.05% accompanied with a high photovoltage are achieved for M142‐ and M143‐based doped devices, respectively, outperforming the controlled cells based on nonsubstituted carbazole HTM (M145, PCE = 17.25%). Moreover, the devices based on M143 exhibit good long‐term storage, thermal, and light stability. This work provides a simple strategy for molecular design in developing efficient carbazole donors. Abstract : Cost‐effective carbazole donors toward efficient hole transport materials (HTMs) have been developed based on the arylamine‐carbazole hybrid strategy. The perovskite solar cells based on M143 achieve a power conversion efficiency over 20%, which is among the highest performance for organic HTMs with carbazole donors.